Estimate the Presence of Pathogenic Fungi in the Soil (Albayan Scientific Journal, 2023)
Ten random samples were collected from two sites in the city of Tobruk for the purpose of the study, the first site was from Al-Haj Ahmed Atallah grape farm at the east entrance of the city and the second site was from a Faculty of sciences belonging land and transported immediately to laboratory Botany department for analysis. inoculated on CZAPEK DOX AGAR and incubated at 25±2 C° and observed for 4-7 days after which the different colonies obtained were identified using the slide culture technique. The pathogenic fungal analysis shows that, Mucor sp has the highest frequency of occurrence (33.3 %) followed by Aspergallius spp (32.8 %) then Penicilium spp (22%) Alternaria spp with (20.8 %) Rhizoctonia solani (19.4)   and Fusarium spp (14.9) frequency of occurrence.
Keywords: Pathogenic; Fungal analysis; frequency of occurrence